Prospective Teachers’ Belief of an Ideal Mathematics Classroom: Changes over Time - Dhitta Puti Sarasvati Ramli (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2020)
This research aims to qualitatively portrait the changes of beliefs that the prospective teachers have since they were at the middle of their second year until the end of their third year in university. The data from this research is taken from the reflection the prospective teachers made in February 2017 and an interview done on the same prospective students in May 2019. The research shows that prospective teachers’ belief of an ideal classroom changes over time and their reason is categorized by several reasons such as the courses they take, their experiences when practice teaching students in schools, and also by the exposure they have related to the resources related to teaching and learning mathematics.